(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Tragedy is a dramatic work that depicts the hero’s collision with the world, his death and the collapse of an ideal. But in Shakespeare’s play there is no tragedy of love, the feelings of the heroes triumph, although they themselves die defending their ideal. That is why researchers often call this play a “wrong tragedy,” since the main characters die, but their ideal is preserved. We can say with confidence that this is an optimistic tragedy.